Al-ḥurūf al-muqaṭṭaʿa and Speech Acts - Osman Muzaffer FİDAN (Din ve Bilim Muş Alparslan Üniversitesi İslami İlimler Fakültesi Dergisi, 2023)
The Qur'an invites people to accept a certain belief and live the belief requested to be accepted as a certain way of life. Therefore, basically, the Qur'an is a book that can be read and understood by people. Along with the fact that the Qur'an is a book that can be understood, it has been discussed in the traditions of tafsir and kalam whether the letters at the beginning of the twenty-nine chapters known as “al-ḥurūf al-muqaṭṭaʿa” are meaningful expressions. While some Muslim scholars have said that the letters in question have no meaning, others stated that the letters in question are meaningful expressions, considering that there is no meaninglessness in the Book of Allah. The Qur'an, which invites its addressees to accept a certain way of life and gives orders and advice to its interlocutors in this direction, performs an abundance and variety of speech acts. In addition to discussing whether “al-ḥurūf al-muqaṭṭaʿa” has a meaning or not, it should also be determined whether they have made any verbal action towards their addressees. Speech acts are the verbs that the speaker performs or aims to bring through his/her expressions during a speech. The reason for the verbal verbs that the speaker performs/aims to fulfill in his speech is to do some work and actions for the addressee/listener of the speaker or to make him do it. These verbal actions are performed by the speaker in a speaking environment, primarily to inform the speaker about some propositional situations as the initiator of the conversation, to ensure that the addressee fulfills some orders and stays away from some prohibitions, and to prevent the speaker from some internal situations that he or she has during the speech to inform the addressee and to attract the attention of the addressee, to wait for what he said to be accepted as true by the addressee, to explain to the addressee the situations that he will assume certain responsibilities in the future, and to take the necessary responsibilities. Speech act theory is a theory that explains what the speaker's verbal performances are, how an oral performance can be successful, what the conditions of success are, and what conditions are violated by possible unsuccessful performances in the twentieth century. Although the speech act theory was first developed in the twentieth century by J. L. Austin, it is a theory of everyday language that has been criticized and developed from various aspects, especially by his student J. R. Searle and other philosophers and linguists. Since the last century, when the theory of speech acts was put forward, it has been intensively studied and developed by philosophy, religious sciences, linguistics, and other sciences. The application studies of the theory of speech acts in the language of religion are also the subject of many studies in the West, although it is only recently known in our country. This article shall try to determine whether the letters in question perform any speech acts, considering the data of speech acts; if they are performing a verbal act, it is aimed to show which of them are. Whether the letters have a speech act or not, if they contain a speech act, what these acts are has been examined within the framework of J. L. Austin and J. R. Searle's understandings of speech act.